Technology of computation of reinforced concrete structures/Gelžbetoninų konstrukcijų armatūros automatizuoto skaičiavimo technologija - Jurkša, Arvydas (Journal of Civil Engineering and Management, 2001)
The author has created a new technology for concrete beam, column, slab, wall and shell reinforcement computation according to the finite element program COSMOS/M analysis results and code of practice valid in Lithuania. A brief description of the technology is included in the article. Computer programmes COSARM and COSMAX were designed for slab, wall and shell reinforcement computation. Results can be visualized graphically. New computer programmes BEAM, COSBEAM, COLUMN, COSREC and COSCIR were created for beam and column reinforcement computation. The new technology extremely enlarged the possibilities of the powerful finite element program COSMOS/M and enabled to compute very complicated reinforced concrete structures.Article in Lithuanian.First Published Online: 30 Jul 2012